Berkah dalam Berkhidmah sebagai Etos Kewirausahaan Santriwati dalam Meraih Kesempurnaan dan Kebermaknaan Hidup - Arifin, Samsul (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
The purpose of this study is to describe the motivation for seeking blessings through service (khidmah) among female students (santriwati), which fosters entrepreneurial ethos. This study focuses on experiences (related to integrity and competence) and the meaning of entrepreneurship for women in Islamic boarding schools (pesantren) who dedicate themselves to the business sector of the pesantren. The research employs a phenomenological approach. The study subjects consist of 20 santriwati selected using key informant and purposive sampling techniques. Data analysis includes several stages: describing phenomena, horizontalization, cluster of meanings, essence description, and report writing. The results indicate that khidmah performed by santriwati in the pesantren, believed to bring blessings in life, is characterized by a balance between shalahiyyah and shalih. Shalahiyyah refers to possessing knowledge and skills, such as building networks, being courteous and polite, and responsive. Shalih refers to having moral integrity, such as sincerity, honesty, contentment (qonaah), acceptance (ridha), patience, and trust in God (tawakal). The santriwati interpret their experiences of khidmah as giving meaning and completeness to life. Through khidmah, they perceive life as meaningful for worship and seeking blessings (tabarruk). Additionally, they feel that khidmah enables them to achieve a complete life for the benefit of the pesantren and society. This sense of meaning and completeness encompasses attaining well-being and happiness in both this world and the hereafter. This research is valuable for developing career counseling and entrepreneurial psychology in the context of Indonesian culture, which remains relatively underexplored.